Penerapan Media Ular Tangga Berbantuan Kartu Angka untuk Meningkatkan Keaktifan dan Hasil Belajar Siswa pada Mata Pelajaran Matematika Kelas II - Irfan Rivai; Muflikhul Khaq; Titi Anjarini (Jurnal Kualita Pendidikan, 2022)
This study focuses on the use of snakes and ladders media with the help of number cards in learning mathematics for addition and subtraction. This study aims to improve activity and learning outcomes in the addition and subtraction material for Class II Girijoyo State Elementary School. The research method uses classroom action research (CAR). The subjects of this study were the 10th grade students of the Girijoyo State Elementary School. The results of the pre-cycle research showed that the percentage was 66.5%, the first cycle increased to 76.5%, and the second cycle increased to 84%. This can be interpreted, that through the observation of the activeness of the second grade students, the success indicator has reached 90% and is categorized as active. In addition to the results of observations, the tests that have been carried out have also increased, from the percentage in the pretest 30% of students who completed the KKM, in the posttest 1 in the first cycle, the percentage increased to 50% of the students who completed the KKM. In posttest 2 in cycle II the percentage of students' completeness rose to 90%. Thus the achievement of the resulting competence with a percentage of 90% of students categorized as complete, exceeding the indicator of success with the achievement of class competence reaching more than 75%.